(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The report examines the key role of human resources in implementing the digital transformation of business processes in Bulgarian industrial enterprises. The survey was conducted in fifty-eight industrial enterprises in Bulgaria; the participants in the study were 232 HR managers and specialists. The main method of research is the questionnaire and the paper contains the results of the analysis of this questionnaire